Examining the Linguistic Tapestry of Globalization: Structural Borrowings - Kananaj, Anila; Karaj, Engjëllushe (RGSA : Revista de Gestão Social e Ambiental, 2024)
Purpose: Redefining economies, cultures, language dynamics, and societies worldwide, globalization has become one of the hallmarks of the contemporary era. The impact of this phenomenon in language is examined in this article, with a particular emphasis on structural borrowings from English into Albanian.